Investment and input requirements for accelerating food production in low-income countries by 1990 - Oram, Peter; Zapata, Juan Antonio; Alibaruho, George; Roy, Shyamal (International Food Policy Research Institute, 1979)
For this study IFPRI determined what it believe to be the feasible extent and type of investment requirements needed to accelerate food production ona contry-by-country basis. We believe that the judgements made were sound and indicate the policies needed for both the geographic location and physical form of these investments.